The Balance of Neutrophil Extracellular Trap Formation and Nuclease Degradation: an Unknown Role of Bacterial Coinfections in COVID-19 Patients? - Nicole de Buhr (American Society for Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is leading to public health crises worldwide. An understanding of the pathogenesis and the development of treatment strategies is of high interest. Recently, neutrophil extracellular traps (NETs) have been identified as a potential driver of severe SARS-CoV-2 infections in humans. NETs are extracellular DNA fibers released by neutrophils after contact with various stimuli and accumulate antimicrobial substances or host defense peptides.